The Light Inside the Shadow An Anthology of Works by BlueBoard Members - Reynolds, Julia; Allen, Joanne; Anderson, Michelle (ANU Press, 2013)
You are not alone! BlueBoard is an online community for people concerned about mental health problems including depression, bipolar disorder, anxiety, eating disorders, borderline personality and related disorders. There are forums for people working on their own recovery and for friends and family members. The aim of BlueBoard is to enable people to reach out and both offer and receive help. BlueBoard is free, anonymous and available at any time from around the world. The delivery of BlueBoard is supported by funding from the Australian Department of Health.